25.0k views
25 votes
How to distribute this problem:
(x-8)^2 + 16

1 Answer

3 votes

Answer:

We conclude that:


\left(x-8\right)^2+16=x^2-16x+80

Explanation:

Given the equation


\left(x-8\right)^2\:+\:16

First, solve (x - 8)²

Apply Perfect Square formula: (a - b)² = a² - 2ab + b²


a=x,\:\:b=8


\left(x-8\right)^2=x^2-2x\cdot \:\:8+8^2


=x^2-16x+64

so the expression becomes


\left(x-8\right)^2+16=x^2-16x+64+16


=x^2-16x+80 Add the numbers: 64+16=80

Therefore, we conclude that:


\left(x-8\right)^2+16=x^2-16x+80

User Brad Zacher
by
5.4k points